El plano cartesiano y su aplicacin en el clculo de la distancia entre dos puntos - Cordova de Rabanal, Myriam Theolinda (2018)
The objective of this work of professional sufficiency is the study of Cartesian plane: application in calculating the distance between two points; For students in the 4th grade of high School. The same that reflects the level of achievement of the competition: solves problems in a moving and localization way; Reasoning and arguing, generating mathematical ideas, at the same time elaborating and using strategies to find the distance between two points in a coordinate system applying the Pythagorean theorem; Through meaningful learning by correctly solving the problems posed. To stimulate students ' learning achievement they became aware of the importance of the use of GPS (Global positioning System). Global Positioning System, which is a system that allows to determine in all the earth the position of any object (a person, object, a company, a terrain) with an accuracy of up to CM. It also allows to perform the graphical representation of work and to better understand the behavior of certain phenomena with relation between the supply and the demand of a product depending on the position of these graphs.